Epidemiology for public health practice - Friis, Robert H; Sellers, Thomas A (Sudbury, Mass. : Jones and Bartlett, 2004)
Provides comprehensive coverage of all major topics in introductory epidemiology. It includes updated data and statistics essential to understanding the importance of epidemiology to public health. Case studies throughout the book demonstrate to students how epidemiologic principles are applied to current real-life situations and settings
The history and scope of epidemiology -- Practical applications of epidemiology -- Measures of morbidity and mortality used in epidemiology -- Descriptive epideiomiology: person, place, time -- Sources of data for use in epidemiology -- Study designs: ecologic, cross-sectional, case-control -- Study designs: cohort studies -- Experimental study designs -- Measures of effects -- Data interpretation issues -- Screening for disease in the community -- Epidemiology of infectious diseases -- Epidemiologic aspects of work and the environment -- Molecular and genetic epidemiology -- Psychologic, behavioral, and social epidemiology
Includes bibliographical references and index
Keywords: Epidemiology -- Public Health; Epidemiology -- Public health personnel